RISK ANALYSIS IN INTERNATIONAL LOGISTICS: METHODS OF MINIMISING THEM - Мешко, Наталія; Кобченко, Андрій; Казарян, Валерія (SWorldJournal, 2024)
The article explores the current challenges and risks arising in international logistics, as well as the key strategies for their management and minimisation. An analytical review of the main risk factors, including economic, political, social, technolog